Theoretical Investigation of the Passive Transmitter Based on Reconfigurable Metasurface - Yang, Shuai; Zhang, Kuang; Ding, Xumin; Yang, Guohui; Wu, Qun (Frontiers in Physics, 2021)
Wireless communication has become a standard solution to satisfy the ever-increasing demands of information transfer in our daily life. Furthermore, reconfigurable metasurfaces comprised of multiple tunable unitcells have drawn significant attention due to their superior electromagnetic performance, while the desired electromagnetic response can be controlled by computer. We therefore present a prototype of a wireless communication system based reconfigurable metasurface that works in the microwave frequency range. A 2-D periodical array of a reconfigurable metasurface is loaded with a varactor diode to effectively adjust the in-band transmission and reflection coefficients that maintain different far-field electromagnetic characteristics. The reconfigurable metasurface does not radiate electromagnetic waves and only carries information by adjusting its reflection and transmission coefficients. With this reconfigurable metasurface, a passive communication method can be realized.